Overview of emerging technologies in sprinkler irrigation to optimize crop production - Li, Hong; Issaka, Zakaria; Jiang, Yue; Tang, Pan; Chen, Chao (International Journal of Agricultural and Biological Engineering, 2019)
Water saving is an essential part of sprinkler irrigation owing to the impact of climate change and rising energy costs. This review highlights the technologies that are emerging in sprinkler irrigation to optimize crop production. While there have been notable advances in irrigation, the continued progress has occurred by the combination of current status with the postulation of new ideas such as conversion of high-pressure sprinkler to low-pressure ones, incorporation of smart controllers in sprinkler irrigation systems. To enhance the adoption of these technologies, research on the dispersion device is needed to improve the performance of impact sprinklers to efficiently operate at low-pressure conditions. It is also important to study how water savings estimates based on water use, irrigated area, longevity of saving, and level of wasteful irrigation prior to the retrofit obtained from field trials can be extrapolated to other areas with different conditions. Research in the development of optimized method for irrigation scheduling is necessary. This review emphasizes that the status of technologies should be considered a continuum, building on earlier knowledge and progress, and hopefully leading toward optimized crop production in sprinkler irrigated areas. Keywords: sprinkler irrigation technologies, smart controllers, crop water demand, crop production DOI: 10.25165/j.ijabe.20191203.4310 Citation: Li H, Issaka Z, Jiang Y, Tang P, Chen C. Overview of emerging technologies in sprinkler irrigation to optimize crop production. Int J Agric & Biol Eng, 2019; 12(3): 1–9.